2011
DOI: 10.1007/s00248-011-9808-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Active Bacterial Community Involved in Natural Attenuation Processes in Arsenic-Rich Creek Sediments

Abstract: Acid mine drainage of the Carnoulès mine (France) is characterized by acid waters containing high concentrations of arsenic and iron. In the first 30 m along the Reigous, a small creek draining the site, more than 38% of the dissolved arsenic was removed by co-precipitation with Fe(III), in agreement with previous studies, which suggest a role of microbial activities in the co-precipitation of As(III) and As(V) with Fe(III) and sulfate. To investigate how this particular ecosystem functions, the bacterial comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 61 publications
7
59
1
1
Order By: Relevance
“…Our biochemical characterization of the Carnoulès ecosystem (Gard, France) supports the existence of multiple abiotic stresses in accordance with previous observations (Casiot et al, , 2004bBruneel et al, 2011). In particular, osmotic stress, low pH and oxidative stress caused by heavy metals and metalloids may explain the reduction in eukaryotic and prokaryotic diversity observed in such ecosystems (Johnson and Hallberg, 2003).…”
Section: Discussionsupporting
confidence: 73%
“…Our biochemical characterization of the Carnoulès ecosystem (Gard, France) supports the existence of multiple abiotic stresses in accordance with previous observations (Casiot et al, , 2004bBruneel et al, 2011). In particular, osmotic stress, low pH and oxidative stress caused by heavy metals and metalloids may explain the reduction in eukaryotic and prokaryotic diversity observed in such ecosystems (Johnson and Hallberg, 2003).…”
Section: Discussionsupporting
confidence: 73%
“…Metaproteomic data showed that Carnoulès strains indeed express functions protecting against general and oxidative stress, including superoxide dismutase or thioredoxin, and chaperones such as DnaK or GroEL, which have previously been detected in AMD (Ram et al, 2005;Bruneel et al, 2011). Several proteins such as RecA and DPS involved in DNA recombination and repair were also identified.…”
Section: Phylogeny and Genome Reconstructionmentioning
confidence: 93%
“…Remaining clones belonged to Firmicutes (4%) and Acidobacteria (3%), and to a lesser extent to classes such as Spirochaetes (1%) and a-Proteobacteria (1%). This demonstrates that the microbial community at Carnoulès includes a few other bacterial Genomic deciphering of an arsenic-rich ecosystem PN Bertin et al phyla in addition to those previously identified (Bruneel et al, 2006(Bruneel et al, , 2011. To decipher the possible role of microorganisms in the biotransformation of toxic elements present at the study site, total DNA extracted from sediments was next fully sequenced.…”
Section: Phylogeny and Genome Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotic and/or abiotic depositions of the oxidized form Fe(III) give rise to extracellular, ferric oxide-encrusted, spirally twisted stalks (18,21). The Gallionella cells and associated stalks are found ubiquitously in various aquatic environments such as iron seeps (1), creeks (15), groundwater (30), drinking-water distribution systems (35,44), wetland rhizospheres (56), and acid mine drainage (3).…”
mentioning
confidence: 99%